Suspended graphene sensor with controllable width and electrical tunability via direct-write functional fibers - Regmi, Abiral; Shin, Dongwoon; Kim, Jong-Hyun; Choi, Sun; Chang, Jiyoung (ELSEVIER SCI LTD, 2020)
In our study, we report Near-field electrospinning as a novel method of patterning and tuning suspended graphene channel. As a proof of concept, a resistive sensor has been fabricated for the detection of air carrying NH3 gas vapors. The suspended graphene channel, performing as the primary sensing element, changes its resistivity when NH3 molecules are absorbed on the surface of the graphene, effectively functioning as scattering centers. By utilizing the Near-field electrospinning for the deposition of the functional fibers, not only the width of the bridge but also the chemical doping effect on graphene can be readily tuned through the adjustment of process parameters and implementation of a wide range of polymers. About 78 % boost in sensitivity is confirmed when the width of suspended graphene channel is decreased from 15 mu m to 5 mu m. The presented process is expected to provide a simple, cost-effective and one-step precise manufacturing method by easily creating suspended graphene channels for a wide range of sensing applications not just limited to gas detection.
Keywords: BENDING INSTABILITY; FIELD; TRANSPORT; CARBON